A Neuregulin‐1 schizophrenia susceptibility variant causes perihippocampal fiber tract anomalies in healthy young subjects. Issue 2 (19th January 2014) - Nickl‐Jockschat, Thomas; Stöcker, Tony; Krug, Axel; Markov, Valentin; Huang, Ruiwang; Schneider, Frank; Habel, Ute; Eickhoff, Simon B.; Zerres, Klaus; Nöthen, Markus M.; Treutlein, Jens; Rietschel, Marcella; et al.
Abstract Background Changes in fiber tract architecture have gained attention as a potentially important aspect of schizophrenia neuropathology. Although the exact pathogenesis of these abnormalities yet remains to be elucidated, a genetic component is highly likely. Neuregulin‐1 (NRG1) is one of the best‐validated schizophrenia susceptibility genes. We here report the impact of the Neuregulin‐1 rs35753505 variant on white matter structure in healthy young individuals with no family history of psychosis. Methods We compared fractional anisotropy in 54 subjects that were either homozygous for the risk C allele carriers (n = 31) for rs35753505 or homozygous for the T allele (n = 23) using diffusion tensor imaging with 3T. Tract‐Based Spatial Statistics (TBSS), a method especially developed for diffusion data analysis, was used to improve white matter registration and to focus the statistical analysis to major fiber tracts. Results Statistical analysis showed that homozygous risk C allele carriers featured elevated fractional anisotropy (FA) in the right perihippocampal region and the white matter proximate to the left area 4p as well as the right hemisphere of the cerebellum. We found three clusters of reduced FA values in homozygous C allele carriers: in the left superior parietal region, the right prefrontal white matter and in the deep white matter of the left frontal lobe. Conclusion Our results highlight the importance of Neuregulin‐1 for structural connectivity of the right medial temporal lobe. This finding is in line with well known neuropathological findings in this region in patients with schizophrenia.